Conceptual comparison of four configurations in the thermal coupling of ammonia synthesis and 2-butanol dehydrogenation. (25th May 2019) - Ghani, Roozbeh; Iranshahi, Davood
Highlights: Simultaneous production of ammonia and MEK in thermally coupled reactors. Series-parallel configurations are compared. Thermal Integration of MEK and ammonia plants. 2-butanol conversion and MEK production are increased by this new configuration. Supplying the required hydrogen for ammonia synthesis by 2-Butanone dehydrogenation. Abstract: In this study, simultaneous production of ammonia and methyl ethyl ketone (MEK) based on thermal coupling idea is analyzed in four different configurations by considering various feeding modes. Ammonia synthesis, as the exothermic reaction, performs in the inner tube of the proposed thermally coupled reactor, while MEK and hydrogen are produced by the endothermic dehydrogenation reaction of 2-butanol in the outer tube. As a result of heat transfer between tubes, inter-stage coolers and furnace which were required for the ammonia synthesis and 2-butanol dehydrogenation plants are eliminated, respectively. Besides, the produced hydrogen is employed to supply 60.91%, 62.89%, 63.49%, and 64.19% of the required hydrogen for ammonia synthesis in each configuration. Therefore, a significant decrease in capital and operational costs as well as energy saving and removing furnace emissions like CO, CO2, and NOx are achieved. Based on the simulation results, series feeding on the ammonia synthesis and parallel feeding on the 2-butanol dehydrogenation showed the maximum nitrogen conversion, ammonia production and yield, while series-series feeding resulted in the best performance from the 2-butanol conversion, MEK production, and yield viewpoint. Finally, the two aforementioned configurations were optimized by applying the multi-objective optimization method.